2011
DOI: 10.1111/j.1600-0579.2010.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of quality and feasibility of an objective structured clinical examination (OSCE) in preclinical dental education

Abstract: The OSCE is reliable and valid in the context of preclinical dentistry. The cost is substantial. The problem of improvement of students' results with ascending circuit number has to be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 32 publications
0
37
0
6
Order By: Relevance
“…There are many examples of use in dental disciplines: pre-clinical phase [86], [87], [88], orthodontics [89], [90], oro-maxillofacial surgery [91], [92], [93], restorative dentistry [87], [94], [95], [96], parodontology [97], clinical prosthetics [86], pediatric dentistry [98], radiology [99], microbiology [94], [97]. …”
Section: Discussionmentioning
confidence: 99%
“…There are many examples of use in dental disciplines: pre-clinical phase [86], [87], [88], orthodontics [89], [90], oro-maxillofacial surgery [91], [92], [93], restorative dentistry [87], [94], [95], [96], parodontology [97], clinical prosthetics [86], pediatric dentistry [98], radiology [99], microbiology [94], [97]. …”
Section: Discussionmentioning
confidence: 99%
“…At the end of the semester, each student took the written exam, which was analyzed (mean, median, mode) separately for each year. [21][22][23][24][25][26][27] The validity was measured using Pearson correlation. Each system was analyzed to understand any deficits in the courses.…”
Section: Discussionmentioning
confidence: 99%
“…The R 2 coefficient is used to measure the proportional change in the dependent variable (the checklist score) by changes in the independent variable (the global grade); this is a marker of internal consistency. [21][22][23][24][25][26] The final method for establishing the validity of the exam is the comparison of the OSCE scores with written exam scores using Pearson correlation. [27] In Saudi Arabia, King Saud University and King Abdulaziz University were the first Saudi universities to published their experiences about using the OSCE in the field of surgery, which was reported in detail by Al-Naami [28] at King Saud University (for students in their final year).…”
Section: Introductionmentioning
confidence: 99%
“…Classifying all the stations into "dental materials" and "non dental materials" may strengthen evidence of validity based on internal structure, as Eberhard et al showed that students who performed well in the dental material stations achieved poorer results in non-material stations and vice versa (Eberhard et al, 2011).…”
Section: Internal Structurementioning
confidence: 99%